'How dare she?!': Parrhesiastic resistance and the logics of protection of/in international security. (August 2022) - Châteauvert-Gagnon, Béatrice
Malalai Joya, Greta Thunberg, Idle No More leaders – what do these figures have in common? They each decided to act/speak out against the failures, lacks, exclusions, violence and injustices in the words and deeds of different authorities claiming to act on behalf of (their) security and protection, and thus made visible, challenged and disrupted the dominant logics of protection on which such claim is based. More specifically, they each enacted this critique by performing a contemporary form of parrhesia – a practice in Ancient Greece that consisted in speaking truth frankly and courageously to power, taking risks in doing so out of a sense of duty to improve a situation for oneself and others. Yet none of these women stated anything radically new or shockingly unknown. So why, then, did speaking truths that were already known lead to such dire consequences and intense reactions? This article will argue that by mobilizing the frameworks of logics of protection and parrhesia together, we can have a fuller understanding of these figures' dissident truth-speaking: it is precisely their positionings within logics of protection that made their truths so daring and, in turn, it is through parrhesia that Joya, Thunberg and Idle No More activists made logics of protection visible through their disruption, opening up potentialities for 'doing' and 'being' otherwise. The dual framework offered in this article thus offers interesting avenues through which to explore resistance, truth and protection in (feminist) security studies today.